Perundangan persekolahan di Malaysia, 1950-1997 - Jamil Halim; Othman Dahlan; Syapela Grafik Sdn. Bhd. (Kuala Lumpur : Syapela Grafik, 1998)
Law and regulations with reference to education in Malaysia.
Includes index.
English and Malay.
Keywords: Educational law and legislation -- Malaysia